Estudio de factibilidad y sostenibilidad para una cooperativa de ahorro y crédito al servicio de los, agricultores, artesanos y microempresarios del cantón Quinsaloma, año 2013 - Naranjo Gomez, Jenny Lorena (2013)
This research was done in order to meet feasibility and sustainability for a credit union, designed to meet the financial needs of farmers, artisans and entrepreneurs Quinsaloma Canton. The inhabitants are mostly engaged activities such as agriculture, trade, handicrafts and small industries. Although this county has a State Bank (BNF) this does not provide the necessary support and timely requiere. Se which then makes urgent the creation of a new financial institution that provides these services according to the current needs of this canton. The method used in the research was inductive - deductive data from collection through field research allowed to analyze the facts and results of observation and the survey data also allowed interpreting and generalizing the results so logic, which allowed testing the hypothesis. For data collection, we used direct observation and structured survey, the questionnaire and entrevista después having performed the research concludes that there is a 85% of people interested in the total sample for research purposes. Economic indicators allowed the calculation of the net present value (NPV) from the net cash flows, with a discount factor of 16% which gave a positive NPV of $ 28,392.2, which means it is attractive to invest in this project. With the foregoing background, we performed the calculation of the internal rate of return, which was applied to the formula of the TIR Interpolated. To find it we proceeded to calculate the Net Present Value (NPV) was obtained as a result interpolating an Internal Rate of Return (IRR) of 54.67%, and the same is greater than the rate of chance and therefore is suitable invest in the project. CAl relate the benefits and costs to date, we applied a chance rate of 16% yields a cost-benefit (RB / C) equal to $ 1.14 of profit.